PENGARUH LABA BERSIH DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Dewi Setiawati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this study was to prove empirically the effect of net income and operating cash flow on the price of sahan on Food and Beverages Companies listed on the IDX for the 2012-2015 period. The object of the research was conducted on Food and Beverages companies listed on the IDX for the 2012-2015 period. The sample selection method used is purposive sampling and the selected sample is 10 companies multiplied by 4 years so that there are 40 company data. This study uses secondary data and is assisted by the SPSS version 16 statistical test tool. The results showed that H1 has a significant effect on stock prices (Y). This is evidenced by the results of t-count of -2.146 with a significance value of t (0.039) <0.05 and H2 does not significantly influence the stock price (Y). This is evidenced by the results of t-count 1.809 with a significance value of t (0.079)> 0.05. Simultaneously shows that H3 has no significant effect on stock prices (Y). This is evidenced by the F-count result of 2.679 with a significance value of F (0.082)> 0.05. The conclusion of the study shows that H3 simultaneously does not have an influence on stock prices because investors realize that stock prices are not only affected by net income and operating cash flow but also influenced by other factors.